Manajemen Pembiayaan Pendidikan dalam Perspektif Teori Penganggaran Partisipatif - Sarjono; Nurfuadi (Program Studi Pendidikan Agama Islam, Universitas Muhammadiyah Bandung, 2024)
This study aims to explore the Management of Education financing in the perspective of participatory budgeting theory. In the context of Islamic Education, effective financing management is very important to ensure the sustainability and quality of Education. This study uses a qualitative method with a case study approach, which focuses on data collection through observation, interviews, and documentation in several Islamic Education institutions. The results of the study indicate that Community participation in Education financing can increase transparency and accountability in fund management. The identified management includes diversification of financing sources such as funds from the government, zakat, waqf, infaq, and Community donations. In addition, the importance of preparing a realistic annual budget based on the operational needs of the institution is also emphasized. The financing planning process is carried out through an analysis of the needs and potential of the Community, while the implementation involves mobilizing resources and funds collaboratively. Evaluation is carried out by comparing the budget plan with the realization of the use of funds to ensure that all activities run in accordance with the principles of budget transparency. Through this research, it is expected to contribute to the development of a more effective and sustainable Islamic Education financing management model, as well as being a reference for other educational institutions in implementing similar Management.